Influence of Product Quality on Purchase Decision at PT Pertani (Persero) UPP Sidrap Regency - Pandi Putra (Amsir Management Journal, 2022)
This study aims to determine and analyze how much influence product quality has on purchasing decisions at PT. Pertani (Persero) UPP Sidrap Regency. The analytical methods used in this study were observation, interviews, questionnaires, and documentation. The method of determining the sample is using the Roscoe formula as many as 70 respondents. The analytical method used is the method of multiple linear analysis. This method is processed using SPSS version.23. Based on the results of the research that has been done, where the results of multiple linear regression obtained Y = 2.263 + 0.257 (X 1) + 0.009 (X 2) + 0.013 (X 3) + 0.132 (X 4) + 0.011 (X 5) + 0143 (X 6) + e. In addition, with the F test (simultaneous) it can be seen that performance, durability, suitability, reliability, features, design have a significant influence on purchasing decisions with a significant level of 0.000 < 0.05. Based on the t-test (partial), of all the independent variables, only the performance variable is indicated by the value of tcount (6.852) > (1.998) with a significant probability of (0.000) < (0.05). While the design variable is indicated by the value of tcount (3.077) > (1.998) with a significant probability of (0.003) < (0.05). While other variables such as durability, suitability, reliability, and features have no significant effect on purchasing decisions.